Workplace accident risk analysis using the bowtie method in the construction industry: a literature review - Fajrisa, Deva; Hariyono, Widodo; Sulistyawati, Sulistyawati (Sean Institute, 2024)
Occupational Health and Safety (OHS) is an important aspect of decent work, with work accident statistics assessing worker protection from hazards and risks. The construction industry, which has a high risk of accidents, requires effective risk management, including bowtie analysis. This research analyzes the use of the bowtie method in the construction industry in Indonesia. A systematic review with a PRISMA approach was conducted. Relevant articles were searched during the period 2018-2023 through Sinta, Google Scholar, and PubMed using predefined inclusion and exclusion criteria, namely